Consequences of untreated dental caries in children aged 36 to 71 months in the province of Yauyos - Bustos de la Cruz, Juana Rosa (2023)
Objective: To determine the clinical consequences of untreated dental caries in children aged 36 to 71 months in the province of Yauyos. Materials and Methods: The study was descriptive, observational and cross-sectional, the sample was 100 girls and boys from 36 to 71 months of age from cribs-gardens, whose teeth were evaluated per arch using the pufa index. Cramer's V test was used for data analysis. Results: The clinical consequences of untreated caries was 59.0% according to the pufa index with a higher frequency in girls (57.4%) and those who were between 60 and 71 months of age were the most affected (75, 0%). According to the dental arches and type of condition, 51.2% of the teeth in the upper arch presented clinical consequences of untreated dental caries, of which the condition with the highest prevalence was pulpitis in both arches, 55% in the upper and 57% at the bottom. Conclusions: Girls and boys from 36 to 71 months of age in the province of Yauyos present the four conditions of the clinical consequences of untreated dental caries.